Iron Nanoparticles: Lithiumpyridinyl‐Driven Synthesis of High‐Purity Zero‐Valent Iron Nanoparticles and Their Use in Follow‐Up Reactions (Small 37/2019). Issue 37 (11th September 2019) - Egeberg, Alexander; Block, Theresa; Janka, Oliver; Wenzel, Olivia; Gerthsen, Dagmar; Pöttgen, Rainer; Feldmann, Claus
Abstract : In article number1902321, Claus Feldmann and co‐workers present the formation of zero‐valent iron nanoparticles (Fe 0 ) by lithium pyridinyl‐driven reduction of FeCl3 (Fe +III ) in pyridine and their subsequent use as reactive starting material to obtain FeCp * 2 (Fe +II, Cp * : pentamethylcyclopentadienyl). The novel pyridine‐based synthesis of reactive Fe 0 nanoparticles as well as further follow‐up reactions with reactive Fe 0 nanoparticles as precursors are presented.